2022
DOI: 10.3390/curroncol29090482
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Celecoxib in Addition to Standard Cancer Therapy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The purpose of this meta-analysis was to evaluate the efficacy and safety of celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, in addition to standard anticancer therapy. Randomized controlled trials (RCTs) that evaluated the efficacy and safety of celecoxib-combined cancer therapy were systematically searched in PubMed and Embase databases. The endpoints were overall survival (OS), progression-free survival (PFS), disease-free survival (DFS), objective response rate (ORR), disease control rate (DCR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…COX-2/PGE2 is an attractive therapeutic target, as it acts on multiple cell types within cancers and can also be induced by conventional chemotherapy ( 54 , 72 ). Combination of celecoxib with other chemotherapies including taxanes have been tested in preclinical models and clinical trials and showed some indication of efficacy ( 73 , 74 ). However, these trials revealed an unmet need for biomarkers to better identify which cancers may respond to combination treatments that include celecoxib ( 75 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…COX-2/PGE2 is an attractive therapeutic target, as it acts on multiple cell types within cancers and can also be induced by conventional chemotherapy ( 54 , 72 ). Combination of celecoxib with other chemotherapies including taxanes have been tested in preclinical models and clinical trials and showed some indication of efficacy ( 73 , 74 ). However, these trials revealed an unmet need for biomarkers to better identify which cancers may respond to combination treatments that include celecoxib ( 75 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecules targeting Wnt pathway such as PRI-724 [ 163 ] (a β-catenin antagonist), LGK-974 [ 164 ] (a porcupine inhibitor) and Vantictumab [ 165 ] (an anti-FZD antibody) are in early clinical trials for the treatment of leukemia, melanoma, colorectal carcinoma and cancers of breast, lung, and pancreas [ 118 ]. In addition, two FDA-approved non-steroidal anti-inflammatory drugs (NSAIDs), namely sulindac [ 166 ], that also targets DVL, and celecoxib [ 167 ], that also inhibits β-catenin signaling, are under early clinical trials for their antineoplastic activity.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…PGE2 induces arginase expression in a mouse model of lung cancer and inhibiting COX-2 can lead to a lymphocyte-mediated anti-tumour response ( 242 ). A large meta-analysis, across multiple tumour types, showed modest benefits ( 238 ) in adding the selective COX-2 inhibitor celecoxib to standard anticancer therapy with no concerning toxicity ( 230 ). Celecoxib has been used in a phase I trial combined with radiotherapy in NPC with encouraging outcomes and no clear toxicity, however, this trial did not report on the effect of EBV positive versus negative tumours or look at MDSC numbers or function ( 243 ).…”
Section: Mdsc Targeted Therapymentioning
confidence: 99%